Is intensive gait training feasible and effective at old age? A retrospective case-control study on the use of Lokomat Free-D in patients with chronic stroke. (October 2021) - Manuli, Alfredo; Maggio, Maria Grazia; Stagnitti, Maria Chiara; Aliberti, Riccardo; Cannavò, Antonino; Casella, Carmela; Milardi, Demetrio; Bruschetta, Antongiulio; Naro, Antonino; Calabrò, Rocco Salvatore
Highlights: As population ages, specialized treatment are needed to improve elderly QoL. Robotics has proven effective in improving functional recovery in neurological patients. Old patients may benefit from high-intensity robotic rehabilitation using the Lokomat-Pro FreeD. Abstract: Background: In the last decade, the number of people over 60 has increased, leading to various healthcare problems. The aim of this retrospective study is to evaluate the effects of robotic rehabilitation in elderly patients as well as their perception of usability and adaptation to intensive robotic neurorehabilitation. Methods: This is a retrospective case-control study. Eighty elderly stroke patients were included in the analysis using an electronic data retrieval system. The enrolled patients were divided into two groups: the experimental group (EG) underwent rehabilitation training with Lokomat FreeD, equipped with a VR screen, while the control group (CG) performed traditional rehabilitation training. The two groups matched for age, sex, education, brain injury, stroke interval. The rehabilitation protocol included a total of 40 training sessions. Results: Both types of rehabilitation led to an improvement in the perceived level of disability (FIM) and in the performance in gait and balance (TT), highlighting a significant improvement especially in the EG. However, only in the EG, Lokomat training had induced an increase in the distance covered in 10 min (10 m walk test), and a significant improvement in mood (HRS-D). Moreover, Lokomat-FreeD was well tolerated by patients with high levels of usability. Conclusions: Our results suggest that elderly patients may benefit from high-intensity robotic neurorehabilitation using the Lokomat-Pro FreeD.